The Use of Methylphenidate in the Postoperative Management of Older Adults after Coronary Artery Bypass Surgery. Issue 2 (14th March 2016) - Piercecchi, Chris W.; Vasquez, Julio C.; Kaplan, Stephen. J.; Mispireta, Monica L.; DeLaRosa, Jacob
ABSTRACT: Objective : Apathy and depression are common in older adult patients following open-heart surgery and contribute to delayed early mobility. The stimulant methylphenidate has not been widely studied in the older adult population. The aim of this study was to investigate differences in short-term outcomes between older adults who received methylphenidate following coronary artery bypass (CABG).Methods : In this retrospective cohort study, patients who underwent isolated CABG at a single community hospital were reviewed. All patients ≥70 years old were included. Groups were defined by whether or not they received postoperative methylphenidate (PM). Univariate and multivariate analysis was conducted. A generalized linear model predicting hospital length of stay (LOS) was constructed.Results : Of the 150 patients reviewed, 50 were included. Median age was 75.5 years (IQR 72–79). Seven patients were women. Twenty-seven patients received PM; 23 patients did not (NPM). Both groups had similar baseline and clinical characteristics. PM had shorter LOS (4 [3–5] days vs. 6 [4–7] days, p < 0.001). The association of methylphenidate with shorter LOS remained significant in multivariate analysis (IRR 0.74 [95% CI 0.62–0.87], p = 0.001). Mortality at 30-days was zero in both groups.Conclusions : PM following CABG may be associated with shorter LOS in the older adult population.